Remodeling of Interstrand Crosslink Proximal Replisomes Is Dependent on ATR, FANCM, and FANCD2 - Jing Huang (Cell Reports, 2019)
Summary: Eukaryotic replisomes are driven by the mini chromosome maintenance (MCM [M]) helicase complex, an offset ring locked around the template for leading strand synthesis by CDC45 (C) and GINS (G) proteins. Although the CDC45 MCM GINS (CMG) structure implies that interstrand crosslinks (ICLs) are absolute blocks to replisomes, recent studies indicate that cells can restart DNA synthesis on the side of the ICL distal to the initial encounter. Here, we report that restart requires ATR and is promoted by FANCD2 and phosphorylated FANCM. Following introduction of genomic ICLs and dependent on ATR and FANCD2 but not on the Fanconi anemia core proteins or FAAP24, FANCM binds the replisome complex, with concomitant release of the GINS proteins. In situ analysis of replisomes proximal to ICLs confirms the ATR-dependent release of GINS proteins while CDC45 is retained on the remodeled replisome. The results demonstrate the plasticity of CMG composition in response to replication stress. : Replication of the mammalian genome is driven by the replisome complex, which unwinds DNA and must overcome many impediments. Zhang et al. find that the encounter of the CMG with a strong block triggers a change in replisome composition that is important for restart of replication past the obstruction. Keywords: replication traverse, interstrand crosslink, ICL, ATR, FANCM, FANCD2, CMG, GINS